Eight-channel high-speed electrical impedance tomography device implemented on a programmable system on a chip - Fausto Andrés Escobar; Carlos Felipe Rengifo; Víctor Hugo Mosquera (HardwareX, 2025)
This study proposes an electrical impedance tomography (EIT) device based on a programmable system on a chip (PSoc). The EIT-PSoC system is implemented using two PSoC 5LP platforms. A resistive phantom is used to study frame frequency (fps), accuracy (Ac), and signal-to-noise ratio (SNR). A saline phantom, along with both conductive and non-conductive objects, is employed to evaluate the system’s ability to detect changes in impedance distribution. Finally, the dielectric characteristics of the human lower pelvis is emulated using four agar phantoms, allowing an evaluation of the EIT-PSoC system’s performance in response to changes in fluid volume and conductivity. Experiments conducted on the resistive phantom to characterize the EIT-PSoC system demonstrate a frame frequency of 100 fps, a median SNR of 63.59 dB, and an accuracy of 95.39% when using a 0.98 mA sinusoidal current signal at 50 kHz. EIT image reconstruction shows that the proposed system can distinguish impedance changes in the saline phantom. Additionally, by utilizing the global impedance (GI) index and the agar phantoms, the EIT-PSoC system can detect changes in volume and conductivity, making this system a promising alternative for monitoring the volume and conductivity of biological fluids.